Nafion phosphonic acid composite membranes for proton exchange membranes fuel cells - Teixeira, Fatima (2020)
ABSTRACT: In this work, new doped Nafion membranes with enhanced proton conductivity were prepared to be used as proton exchange membranes in fuel cells. New dopants derived from arylmono-or bisphosphonic acid were prepared and incorporated into the new membranes using impregnation or casting methods. Proton conductivities were assessed by Electrochemical Impedance Spectroscopy (EIS), at different temperatures and relative humidity (RH) conditions, in order to evaluate the influence of the structure and the method of the preparation on proton transport. The membranes prepared by casting showed higher proton conductivities than commercial Nafion membrane at all temperatures and relative humidity conditions studied. The [1,4-phenylenebis-(hydroxymethanetriyl)] tetrakis(phosphonic acid) (BP2) showed the best proton conductivity with a value of 87 mS cm(-1). The values obtained for the activation energy (Ea) for proton conduction suggests that transport occurs via both Grotthuss and vehicular mechanisms.